2023
DOI: 10.3390/biomedicines11020431
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Trimethylamine N-Oxide (TMAO) to Chronic Inflammatory and Degenerative Diseases

Abstract: Trimethylamine N-oxide (TMAO) is a metabolite produced by the gut microbiota and has been mainly associated with an increased incidence of cardiovascular diseases (CVDs) in humans. There are factors that affect one’s TMAO level, such as diet, drugs, age, and hormones, among others. Gut dysbiosis in the host has been studied recently as a new approach to understanding chronic inflammatory and degenerative diseases, including cardiovascular diseases, metabolic diseases, and Alzheimer’s disease. These disease typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…In Metabolic Syndrome related diseases, TMAO was implicated in causing endoplasmic reticulum stress and insulin resistance in patients at risk for diabetes 99 , and also implicated in promoting de novo lipogenesis in the liver of metabolic-dysfunction-associated fatty liver disease 100 . Increased serum levels of TMAO in colorectal cancer are correlated to increased tumors, worse stage and incidence of metastasis and overall lower disease survival 40 . Increasing amount of studies are also highlighting that TMAO may be linked to other cancers as well, such breast, ovarian and gastric cancers 101 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Metabolic Syndrome related diseases, TMAO was implicated in causing endoplasmic reticulum stress and insulin resistance in patients at risk for diabetes 99 , and also implicated in promoting de novo lipogenesis in the liver of metabolic-dysfunction-associated fatty liver disease 100 . Increased serum levels of TMAO in colorectal cancer are correlated to increased tumors, worse stage and incidence of metastasis and overall lower disease survival 40 . Increasing amount of studies are also highlighting that TMAO may be linked to other cancers as well, such breast, ovarian and gastric cancers 101 .…”
Section: Discussionmentioning
confidence: 99%
“…TMAO is a microbial metabolite that is implicated in multiple different chronic inflammatory diseases, including but not limited to kidney diseases, metabolic syndrome and related conditions, cardiovascular disease, and cancer 40 . TMAO causes platelet hyperreactivity, foam cell formation and adhesion, cardiac fibroblast migration and proliferation, and cellular apoptosis that all contribute to cardiovascular disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although activation of AHR with TCDD has been shown to strongly upregulate Fmo3 expression (necessary to produce TMAO) in adult male mice, effects were minimal in juveniles [86], warranting followup studies to determine whether maternal WD exposure has long-lasting effects on the gut microbiome and AHR activity, with potential risks for increased TMAO-associated diabetes and cardiovascular disease [87]. Finally, in vitro studies have shown that TMAO signals through Toll-like receptors (TLRs) and the NLRP3 inflammasome and induces expression of proinflammatory cytokines in macrophages and endothelial cells [92,93]. Whether TMAO in early life plays a role in immune education remains to be determined.…”
Section: Discussionmentioning
confidence: 99%